2019
DOI: 10.3390/nano9010115
|View full text |Cite
|
Sign up to set email alerts
|

Facile Electrochemical Sensor for Nanomolar Rutin Detection Based on Magnetite Nanoparticles and Reduced Graphene Oxide Decorated Electrode

Abstract: A new electrochemical sensor for nanomolar rutin detection based on amine-functionalized Fe3O4 nanoparticles and electrochemically reduced graphene oxide nanocomposite modified glassy carbon electrode (NH2-Fe3O4 NPs-ErGO/GCE) was fabricated through a simple method, and the X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), transmission electron microscope (TEM), vibrating sample magnetometer (VSM) and electrochemical technique were used to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(46 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…TiO 2 NPs can be easily anchored on the surface of metal electrodes [43], but immobilizing them directly on the surface of glass carbon electrodes (GCE) is difficult. Due to their unique properties such as their large surface to-volume ratio, extraordinary electrical conductivity, and rapid electron transfer rate [44][45][46][47][48], graphene (Gr) has been considered as the most preferred electrode material for electrochemical sensors. Its unique 2D crystal structure and electronic property endows itself an ideal catalyst support for the anchoring of metal or metal oxide NPs [49], which offers versatile selective catalytic or sensing properties.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 NPs can be easily anchored on the surface of metal electrodes [43], but immobilizing them directly on the surface of glass carbon electrodes (GCE) is difficult. Due to their unique properties such as their large surface to-volume ratio, extraordinary electrical conductivity, and rapid electron transfer rate [44][45][46][47][48], graphene (Gr) has been considered as the most preferred electrode material for electrochemical sensors. Its unique 2D crystal structure and electronic property endows itself an ideal catalyst support for the anchoring of metal or metal oxide NPs [49], which offers versatile selective catalytic or sensing properties.…”
Section: Introductionmentioning
confidence: 99%
“…Since the experimental discovery of monolayer by Novoselov and Geim [21], GR has attracted much attention due to its unique properties. The applications of GR or GR-based nanocomposites in high sensitivity and high selectivity electrochemical sensors have been widely reported, such as dopamine [22][23][24], 4-nitrophenol [25], rutin [26], tryptophan [27], sunset yellow [28], quinoline yellow [29], glucose [30], serotonin [31], acetaminophen [32], 4-aminophenol [33] and methyl parathion [34] sensors. Although GR has significant electrocatalytic and sensing properties, it has been reported that in most solvents, due to van der Waals interaction and strong π-π stacking, GR nanosheets are clustered together in a short time [35].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of interferences on sensor's performance and recovery ratio of target analyte were also investigated [56,57]. A fixed concentration of 10 copies/ml WSSV was mixed with different matrixes and then similarly detected by the sensor electrode.…”
Section: Detection Of Wssvmentioning
confidence: 99%